Koyak Activesport / Nurazira Abdul Aziz - Nurazira, Abdul Aziz (2020)
KOYAK Activesport will be a new player in the active sportswear industry. The company is made up of popular sport that have come together to form a high-quality brand that represents independence and accomplishment among the action sports. The company is headquartered in Ipoh, Perak. KOYAK Activesport wants to be the official supplier and sponsor of numerous association sports such as football, futsal, basketball, volleyball, running, tennis and fitness. KOYAK Activesport wants to specialize in sport clothing production and distribution. Besides that, KOYAK Activesport decided to enter into football market because football is favourite local sports, obtaining a great success and becoming the leader in Malaysia, consequently also with international success especially in South Asia. KOYAK Activesport main product is sports clothing manufacturer, which specialize produces footwear and clothing for football, futsal, basketball, volleyball, running, tennis, fitness. KOYAK Activesport provides high-quality sportwear that is designed specifically for sports athletes. Footbal jersey, basketball jersey, sport jacket, sport singlet, sport shoes and cap are just a few of the product lines that the company offers.There was an increasing awareness about leading a healthier lifestyle and a growing trend of getting into sports and fitness. Moreover, the popularity of sports activities like the Football World Cup, Olympic Games, Asia Games and SEA Games helped boost the market. Consumers are now looking for fashionable and trendy athletic wear contrasting to their previous needs. Demand for sportswear that aren’t restricted to athletes also grew as the general public’s awareness regarding their health and fitness.KOYAK Activesport can make a big effort on promoting our brands in many different ways. One of the important factors to a successful company is good official internet page, so one of KOYAK Activesport advantages is a good official internet page, because it gives customers to view and purchase their products online. KOYAK Activesport also have very effective service on online customer service with delivery time is 2-7 days and has a 30 day return right. Products on discount are also advantages for KOYAK Activesport. KOYAK Activesport will give discounts for sale that satisfy our customer. KOYAK Activesport has forecasted explosive sales by the end of first two year, increase continually in next three year. The net profit margin will be low in first two year and increase modestly in next three year.